The Commonalities and Differences in Mitochondrial Dysfunction Between ex vivo and in vivo Myocardial Global Ischemia Rat Heart Models: Implications for Donation After Circulatory Death Research - Quader, Mohammed; Akande, Oluwatoyin; Toldo, Stefano; Cholyway, Renee; Kang, Le; Lesnefsky, Edward J.; Chen, Qun (Frontiers in Physiology, 2020)
Heart transplantation is the ultimate treatment option for patients with advanced heart failure. Since hearts from donation after brain death (DBD) donors are limited, donation after circulatory death (DCD) donor hearts could be another source for heart transplantation. DCD process involves ischemia-reperfusion (IR) injury. Mitochondrial dysfunction contributes to IR and is well established in the ex vivo (buffer perfused) ischemia animal model. However, DCD hearts undergo in vivo ischemia with a variable “ischemic period.” In addition, the DCD hearts are exposed to an intense catecholamine surge that is not seen with ex vivo perfused hearts. Thus, the severity of mitochondrial damage in in vivo ischemia hearts could differ from the ex vivo ischemia hearts even following the same period of ischemia. The aim of our current study is to identify the mitochondrial dysfunction in DCD hearts and propose strategies to protect mitochondria. Adult Sprague Dawley rat hearts underwent in vivo or ex vivo ischemia for 25 min. Subsarcolemmal mitochondria (SSM) and interfibrillar mitochondria (IFM) were isolated from hearts following ischemia. We found that both ex vivo and in vivo ischemia led to decreased oxidative phosphorylation in SSM and IFM compared to time control or DBD hearts. The proportion of damage to SSM and IFM, including proton leak through the inner membrane, was higher with ex vivo ischemia compare to in vivo ischemia. Time control hearts showed a decrease in SSM and IFM function compared to DBD hearts. The CRC (calcium retention capacity) was also decreased in SSM and IFM with ex vivo and in vivo ischemia, indicating that ischemic damage to mitochondria sensitizes mitochondrial permeability transition pores (MPTP). Our study found differential mitochondrial damage between the in vivo ischemia and the ex vivo ischemia setup. Therefore, consideration should be given to the mode of ischemia while evaluating and testing myocardial protective interventions targeting mitochondria to reduce IR injury in hearts.